Depositional paleoenvironment and palynological studies on Permian Karoo hydrocarbon source rocks of Siamwiinga and Sianyolo, mid-Zambezi Basin, Zambia - Godfrey Peter Mweemba; Olubunmi Christopher Adeigbe; Marion Kathaleen Bamford; Angela Charles Effiom; Gilbert Mbzighaa Chongwain (Discover Geoscience)
Abstract This study presents high-resolution palynological investigations of thirty-six rock samples from the Siamwiinga and Sianyolo regions of the Permian Mid-Zambezi Basin, Southern Zambia. The aim was to establish biostratigraphic frameworks, characterize the paleoenvironment, and assess the palynological kerogen composition of potential source rocks. Palynological analysis of Madumabisa Mudstone, Shale, and Gwembe Coal Formation samples revealed five distinct palynoassemblages, including Striatopodocarpites–Osmondacites–Thymospora–Laevigatosporites–Gnetaceae pollenites sinuosus, Lundbladispora–Striatopodocarpites, Striatopodocarpites-Scheuringipollenites-Kendosporites striatus, Verrucosisporites-Striatopodocarpites-Scheuringipollenites and Calamospora-Kendosporites, indicative of Late, Middle, and Early Permian ages, respectively. Biostratigraphic correlations with analogous basins in Zimbabwe, Mozambique, Australia, India, Oman, and China were established. The study identified several new taxa, including Kendosporites antiquus, Rhizomaspora radiata, and Hamiapollenites dettmannae. The diverse palynological assemblages and the presence of abundant terrestrial organic matter, particularly from gymnosperms, suggest the potential for hydrocarbon generation within the Permian sediments of the Mid-Zambezi Basin.